ON THE QUESTION OF THE UNITY OF THE NORTHERN CAUCA¬SUS NATIONALITIES’ LITERATURE (Proceedings of Southern Federal University. Philology, 2013)
Musukaeva A.H.Keywords: ethno-cultural basis, historical and cultural community, a literary genre, interference, typology, contact.The problem of genetic, historical and geographical community of literatures of the peoples of the Northern Caucasus is described. This problem is studied in evolutionary and genre paradigms. A comparative study of national types of literature allows revealing both their common features, as well as peculiarities.